Does Timing of Eruption in First Primary Tooth Correlate with that of First Permanent Tooth? A 9-year Cohort Study - Hamidreza Poureslami; Naser Asl Aminabadi; Alireza Sighari Deljavan; Leila Erfanparast; Azin Sohrabi; Zahra Jamali; Sina Ghertasi Oskouei; Kameliya Hazem; Sajjad Shirazi (Tabriz University of Medical Sciences, 2015)
Background and aims. Predicting the teeth eruption time is a valuable tool in pediatric dentistry since it can affects scheduling dental and orthodontic treatments. This study investigated the relationship between the eruption time of first primary and permanent teeth and the variation in the eruption time considering socioeconomic status (SES) in a 9-year population- based cohort study. Materials and methods. 307 subjects were examined at bimonthly intervals during the first and second years of life and then at six-month intervals until the eruption of first permanent tooth. Eruption times of primary and permanent tooth were recorded for each child. A modified form of Kuppuswamy's scale was used to assess the SES. Results. Among 267 subjects completed all follow-ups, the eruption time for first primary and permanent teeth indicated a direct strong correlation; in that one month delayed or early eruption of first primary tooth resulted in 4.21 months delayed or early eruption of first appearing permanent tooth (r = 0.91, n = 267, P <0.001). No significant correlation was observed between the eruption time of first primary and first permanent teeth and SES (P = 0.67, P = 0.75, respectively). Conclusion. The eruption timing for the first primary tooth had a correlation with the first permanent tooth eruption tim-ing, while SES did not have any influence on eruption times.